BARRIERS, STRENGTH AND WEAKNESS OF PRE-PREGNANCY CLINIC SERVICES IN SARAWAK: A QUALITATIVE ANALYSIS FROM PROVIDER PERSPECTIVES - Md Mizanur Rahman; Natazcza Abdul Rahim (Malaysian Journal of Public Health Medicine, 2018)
Pre-pregnancy Clinic (PPC) services is one the plausible efforts towards achieving the Millennium Development Goals. However, various issues still need to be addressed for improvement of the services. Considering this view, an attempt was made to explore the barriers, strength and weakness of current practice of pre-pregnancy clinic services in Sarawak, since the programme has been implemented in this state from the year 2011. This cross-sectional study was conducted at nine selected health care facilities throughout Sarawak. A multistage sampling procedure was adapted to select the health care facilities. An unstructured open-ended questionnaire was administered to get the in-depth perceived views and current practice of pre-pregnancy clinic services. A total of 322 health care providers from nine selected health care facilities gave their feedback. In the present paper, a qualitative analysis was done for the open-ended questions to get in-depth views of barriers, strength and weakness of pre-pregnancy clinic services. The results of the study were narrated in textual form and a thematic analysis was done manually. The identified themes for perceived barriers to the provision of pre-pregnancy care were perception, attitude and acceptance of PPC services, socio-economic issues, services and client factors. The perceived weaknesses of the services are listed under two main themes: working environment and service factors, while, the strength of services produced three thematic areas which are preparation for pregnancy, prevention of mortality and morbidity and comprehensive services. Though pre-pregnancy services are beneficial for society wellbeing, various issues still need to be considered for the improvement of the quality of services. Lack of awareness, no ministerial guidelines or Standard Operating Procedures (SOP) and knowledge pertaining to the services were few of the main areas which need to be pondered upon. Promotional activities and campaigns should be geared up ensuring availability the services to the general population.